2009
DOI: 10.1111/j.1600-0781.2009.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess the efficacy of photodynamic therapy for Japanese patients with actinic keratosis in relation to lesion size and histological severity

Abstract: The present study demonstrated that ALA-PDT might be useful for treatment of Japanese AK. The therapeutic outcome might depend on the lesion size and the histopathological severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 16 publications
1
26
2
Order By: Relevance
“…Previous studies on MAL-PDT have shown complete response rates of 69% to 92% for AKs on the face and scalp of Caucasian populations10,14,15,16,17. To date, there have been insufficient studies on dark-skinned ethnic groups that have demonstrated the efficacy of ALA-PDT for AKs18,19,20,23. Nakano et al18 showed that ALA-PDT is useful for the treatment of AKs in Asians, and its efficacy might depend on the lesion size and histopathological severity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on MAL-PDT have shown complete response rates of 69% to 92% for AKs on the face and scalp of Caucasian populations10,14,15,16,17. To date, there have been insufficient studies on dark-skinned ethnic groups that have demonstrated the efficacy of ALA-PDT for AKs18,19,20,23. Nakano et al18 showed that ALA-PDT is useful for the treatment of AKs in Asians, and its efficacy might depend on the lesion size and histopathological severity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been insufficient studies on dark-skinned ethnic groups that have demonstrated the efficacy of ALA-PDT for AKs18,19,20,23. Nakano et al18 showed that ALA-PDT is useful for the treatment of AKs in Asians, and its efficacy might depend on the lesion size and histopathological severity. However, several treatment sessions (3~6) are needed to achieve a similar efficacy as in Caucasians, and 2 other studies on ALA-PDT reported that its efficacy was 73% to 82%19,23.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations